Digital Evidence Management in the Criminal Justice System: Towards a Fair and Technology-Responsive Legal Framework - Ismail Marzuki; I Gede Widhiana Suarda; Fendi Setyawan; Reece Walters (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
The increasing reliance on digital evidence in criminal justice proceedings poses new challenges for legal systems that were traditionally built to deal with physical and conventional evidence. With the development of information technology, digital data such as electronic communications, digital traces, and cyber forensic artefacts have become an important part of criminal case evidence. This article presents a conceptual analysis of the urgency of fair and technology-responsive digital evidence management in the criminal justice system. Through a literature review of legal theory, international practices, and national regulations, this paper identifies significant legal gaps, particularly in data authenticity, the chain of evidence, the validity of evidence, and the protection of privacy rights. In its novelty, this article proposes a five-pillar model for the governance of digital evidence, encompassing the principles of legality, evidence integrity, procedural justice, legal digital literacy, and institutional accountability, as an integrated framework to strengthen the management of digital evidence in Indonesia. This model provides a systematic approach that not only focuses on the technical aspects of digital forensics but also integrates legal normative standards, institutional capacity building, and the protection of fundamental rights within the criminal justice process. The scientific contribution of this research lies in its effort to bridge the conceptual gap between the principle of procedural justice and digital forensic practices within the criminal justice system, thereby supporting the realization of a legal framework that is responsive, transparent, adaptable to technological advancements, and oriented toward the protection of human rights. Ultimately, this article calls for a legal framework that not only accommodates the characteristics of digital evidence but also protects defendants' fundamental rights in criminal proceedings.